Genetic variants in the integrin gene predicted microRNA‐binding sites were associated with the risk of prostate cancer. Issue 4 (12th October 2012) - Liu, Jiaming; Huang, Jin; He, Yazhou; Liu, Jinnan; Liao, Banghua; Liao, Ga
Abstract microRNAs (miRNA) silence target genes through Watson–Crick based binding to the 3'untranslated regions (3′UTR). Thus, polymorphisms in the miRNA‐binding sites may disrupt this process and play a potential role in cancer pathogenesis. Integrins have been implicated in the genesis and development of many tumors. This study was designed to evaluate the association between five SNP loci in predicted miRNA‐binding sites in five integrin genes and prostate cancer occurrence and prognosis to provide data for screening high‐risk Chinese Han individuals. These five polymorphisms were genotyped by using the high‐resolution melting method (HRM) in 347 Chinese Han prostate cancer patients with long‐time follow‐up together with 367 age‐matched healthy controls. GC carriers of rs11902171 in ITGAv were associated with a decreased risk of prostate cancer (OR 0.57, 95% CI 0.35–0.93). However, no significant difference was detected in genotype distributions of the five SNP loci in the progression‐free survival time of prostate cancer. The ITGAv gene SNP rs11902171 may be potentially associated with the risk of prostate cancer. © 2012 Wiley Periodicals, Inc.